البُعد الحجاجي في الخطاب النّثري من نصيّة الإقناع إلى إقناعيّة الإيقاع (مجلة الواحات للبحوث والدراسات, 2021)
The Research In The World Of Argumentation Tends To Observation The Sources Of Textual And Artistic Persuasion. Perhaps The Absence Of The Rhythmic  Aspect, Especially In The Prose Discourse, Requires That This Study Be Monitored To Show What Is In The Prose Of The First Rhythm And A Argumentation Statement Of This Rhythm In Order To Create Artistic Bonds That Dispel That Prevalent View The Rhythm  Is Devoid Of Any Destination, It Is Not Necessarily   Argumentation,  And This Is What This Brief Study  Refutes. Its Modern Concept Of Argumentation As A Methodological Equivalent Of The New Rhetoric And Its Conclusion Is Analysis Of Some Rhythmic Examples And A Statement Of The Rhythmic Structure Of The Prose Discourse. Key Words-Argumentation, Discoure, Persuasion, Rythm , Intentionality.